2022
DOI: 10.1111/inr.12748
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact on care professionals due to the SARS‐Cov‐2 virus in Spain

Abstract: To analyze the psychological impact of the SARS-Cov-2 pandemic on nurses in Spain in three different dimensions: exposure to stressors, perceived emotions, and stress coping. Background: On March 11, 2019, the World Health Organization recognized a global pandemic caused by a SARS-Cov-2 virus, COVID-19, which rapidly spread across the planet, involving a community health emergency of international scope. Introduction: The pandemic situation in health centers has led to significant changes in the work environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A study from Spain also showed that being older, not being single, living in an independent house and having more than 15 years of working experience protected against stressors and perceived emotions, and were associated with a greater use of coping techniques [ 30 ]. They also found a greater impact of perceived negative emotions among auxiliary nurses than among university graduated nurses, which is in line with our findings that CoV nurses with high-school diplomas used avoidance coping significantly more than their colleagues with bachelor’s degrees.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Spain also showed that being older, not being single, living in an independent house and having more than 15 years of working experience protected against stressors and perceived emotions, and were associated with a greater use of coping techniques [ 30 ]. They also found a greater impact of perceived negative emotions among auxiliary nurses than among university graduated nurses, which is in line with our findings that CoV nurses with high-school diplomas used avoidance coping significantly more than their colleagues with bachelor’s degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Spain is one of the most affected countries worldwide, with high rates of patients diagnosed, hospitalized, and deceased due to COVID-19 infection [ 2 ]. Different characteristics such as advanced age, male sex or some chronic diseases seem to increase the risk of more severe disease due to SARS-CoV-2 [ 3 , 4 , 5 , 6 ]. Landsteiner ABO blood groups were described on the basis of carbohydrate epitopes, which are present on the surface of erythrocytes and in many other types of human cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors increase the risk of mental health issues, including exposure to social, economic, geopolitical, and environmental circumstances. Mental health risks and protective factors are found in society at different scales, although, the most vulnerable people have taken the greatest impact ( 10 ). Global threats increase the risk of mental illness, including disease outbreaks, humanitarian emergencies, and forced displacement, among others ( 8 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has left great changes in its waves, with an impact on the mental health of people. Therefore, it is important to design and adopt protection strategies for the mental health of health professionals, as well as the early diagnosis of possible mental health problems ( 10 ).…”
Section: Introductionmentioning
confidence: 99%